Relationship between Aging and Renal Function: A Positron Emission Tomographic Study - YAMASHITA, Masato; MIZUKAWA, Norihiko; INABA, Tadashi; USHIJIMA, Yo; FURUYA, Seiichi; ODA, Yohei; NAKAGAWA, Shuichi; NAKAHASHI, Hisamitsu (RADIOISOTOPES, 1990)
Blood volume (V), blood flow (F) and glomerular filtration rate (GFR) per 100 g (100 ml) of kidney were calculated with C15O, H215O and 68Ga-EDTA, to study age-related changes per unit tissue in 19 subjects using positron emission tomography. Age was negatively correlated with V, F and GFR. The agingrelated decrease in V was less marked than those in F and GFR. Analysis by regression formula induced that F, GFR for subjects in their 70 s are 76%, 46% and 55% for those in their 20 s, respectively.